Catalyzing small and medium-sized enterprise venture capital in Sri Lanka. - Kulasinghe, Sharini (Asian Development Bank, 2018)
Small and medium-sized enterprises (SMEs) are the bedrock of Sri Lankas economy. Comprising 75% of all active enterprises, Sri Lankas SMEs provide 45% of employment and contribute 52% to its gross domestic product. Creating an environment conducive to SME growth is integral to achieving equitable economic growth in Sri Lanka. Against this backdrop, this paper seeks to evaluate the viability of supporting the SME sector by improving access to equity or risk capital. This paper highlights market assessment of SMEs and SME finance in Sri Lanka currently, presents documentation of international precedents, and provides an analysis of fund structuring considerations. It presents recommendation for a government-initiated venture capital fund for SMEs in Sri Lanka.